High Migratory Survival and Highly Variable Migratory Behavior in Black-Tailed Godwits - Senner, Nathan R.; Verhoeven, Mo A.; Abad-Gómez, José M.; Alves, José A.; Hooijmeijer, Jos C. E. W.; Howison, Ruth A.; Kentie, Rosemarie; Loonstra, A. H. Jelle; Masero, José A.; Rocha, Afonso; Stager, Maria; Piersma, Theunis (Frontiers in Ecology and Evolution, 2019)
Few studies have been able to directly measure the seasonal survival rates of migratory species or determine how variable the timing of migration is within individuals and across populations over multiple years. As such, it remains unclear how likely migration is to affect the population dynamics of migratory species and how capable migrants may be of responding to changing environmental conditions within their lifetimes. To address these questions, we used three types of tracking devices to track individual black-tailed godwits from the nominate subspecies (Limosa limosa limosa) throughout their annual cycles for up to five consecutive years. We found that godwits exhibit considerable inter- and intra-individual variation in their migratory behaviour across years. We also found that godwits had generally high survival rates during migration, although survival was reduced during northward flights across the Sahara Desert. These patterns differ from those observed in most other migratory species, suggesting that migration may only be truly dangerous when crossing geographic barriers that lack emergency stopover sites and that the levels of phenotypic flexibility exhibited by some populations may enable them to rapidly respond to changing environmental conditions.